Safety and efficacy of Chinese herbal bath for psoriasis vulgaris: A protocol for systematic review and meta-analysis - Lin, Wenxia (Medicine (Baltimore), 2020)
BACKGROUND: Psoriasis is a common, chronic, and recurrent skin inflammatory disease, with psoriasis vulgaris considered as the most prevalent type of psoriasis. Chinese herbal bath, a type of traditional Chinese medicine, is an external therapy widely used to treat psoriasis vulgaris in China, and it has achieved satisfactory clinical effects. However, there are few studies evaluating the safety and efficacy of Chinese herbal bath compared with other external therapies administered under similar conditions. The purpose of this study is to comprehensively evaluate the clinical safety and efficacy of Chinese herbal bath in the treatment of psoriasis vulgaris through a systematic evaluation of the literature, so as to provide a reference basis for future clinical applications. METHODS: PubMed, Embase, CENTRAL, the Web of Science, the China Biology Medicine Database (CBM), the China National Knowledge Database (CNKI), the Wan Fang Database, and the Chong Qing VIP Database will be searched to collect randomized controlled trials of Chinese herbal bath used to treat psoriasis vulgaris. The search time limits will be from the establishment of the database to December 2019. Two researchers will independently screen the studies, extract data, and evaluate the risk of bias of the studies. Meta-analysis will be carried out with the RevMan5.3 software. The mean difference will be used as the effect index for the measurement data, and the odds ratio will be used as the effect index for the enumeration data. The 95% confidence interval will be provided for each effect. Heterogeneity among the results of each study will be evaluated by the Chi-square test. RESULTS: This study will comprehensively evaluate the clinical safety and efficacy of Chinese herbal bath in the treatment of psoriasis vulgaris, so as to provide a reference basis for future clinical applications. CONCLUSION: This study will provide a theoretical basis for the standardized administration of Chinese herbal bath. OSF REGISTRATION NUMBER: doi: 10.17605/OSF.IO/4HRPJ